Reproductive Health Education through Video and Leaflet Increased Knowledge and Attitudes of Junior High School 1 Lobalain Students - Sinlaeloe, Ervina Betsi Cahyani; Nayoan, Christina R; Sir, Amelya B (Journal of Public Health for Tropical and Coastal Region, 2024)
Abstract Introduction: Adolescents’ knowledge about puberty is very important to prevent health problems such as unwanted pregnancies, early marriage, abortion and Sexual Transmitted Infections (STI’s). Thus, health education to increase awareness is really needed. This research aimed to determine the effect of reproductive health education through video and leaflet media on Lobalain 1 junior high school students.  Methods: This quasi-experimental study with pre and post-test design approaches was conducted on 184 junior high school students, who were selected using a stratified random sampling technique. Subjects were divided evenly into 2 groups, who received reproductive health education through video and leaflet and the control group. Knowledge and attitude data were collected through questionnaires. Data were analyzed by chi square tests, with a significance level of < 0.05.Results: The subjects were students aged 12-17 years in grades 7 to 9. In the experimental group there was a significant increase in good knowledge scores category from 20% to 77% (p<0.05), while there was no increase (28% to 30%) in the control group. In the experimental group, the positive attitude score category also significantly increased from 64% to 83% (p<0.05), while in the control group the positive attitude score category did not increase significantly (from 59 to 66%).Conclusion: Health reproduction education through video media and leaflet increased knowledge and attitude of Lobalain 1 junior high school students. It is recommended that local governments and schools increased health promotion efforts in adolescents.